An In silico Approach to Identify a Potential Phyto-Herbicide Candidate against 5- Enolpyruvyl Shikimate-3-Phosphate (EPSP) Synthase - Yongpisanphop, Jiraporn (Science & Technology Asia, 2023)
Crop contamination with chemical herbicide residues is one of the major problems on a global scale. Bioherbicides have been accepted as a promising material to be used in weed control. This study aims to find a potential phyto-herbicide candidate using an in silico approach. A 2D similarity search was used to find the natural compounds having a chemical structure similar to that of glyphosate against natural compound databases. Then, phyto-herbicide candidates were confirmed via molecular docking and property screening. 2-Phosphoglycerate, C00000123, was selected as the potential phyto-herbicide candidate based on the lowest binding energy (-6.45 kcal/mol) similar to that of the reference glyphosate (-7.42 kcal/mol), and it was not a substrate of EPSP synthase. The binding pattern between 2-Phosphoglycerate and EPSP synthase was similar to that of glyphosate binding via Lys22, Lys411, Gly96, Arg124, Arg344, and Arg386. Moreover, 2-Phosphoglycerate had a herbicide-likeness property and was an enzyme inhibitor. It was produced in Oryza sativa L. Therefore, 2-Phosphoglycerate displayed an effective inhibition. However, further wet-lab experiments must be performed to validate the herbicide effectiveness of 2-Phosphoglycerate, and its role as an effective phyto-herbicide inhibitor.